Perception of patients with skin lesions about nursing care in the light of Peplau (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To understand the perceptions of patients with skin lesions about nursing care in the light of Peplau's theory. Method: Qualitative descriptive research carried out from November 2021 to February 2022, with patients treated in a reference outpatient clinic. The data were collected using an interview script, transcribed into a textual corpus, analyzed using Iramuteq software and interpreted using Hildegard Peplau's theory of interpersonal relationships in nursing. Results: The textual corpus consisted of 42 interviews, forming two subcorpora. The first is the origin of skin lesions with the classes: difficult to heal lesion, perceived need and traumatic lesion. The second is the patient's perception of the quality of care provided by the nurse: interpersonal process, exploration, therapeutic process and nursing. Conclusion: The perceptions of patients with skin lesions have shown that the care provided by nursing professionals plays a fundamental role in the therapeutic path to recovery from this health problem, as well as highlighting the considerable contribution that nursing theories can make to the interpretation of the data found.